ASSESSMENT OF ANTIMICROBIAL ACTIVITY OF AZADIRACHTA INDICA FROM MAHALAPURAM, JAIPUR - Mishra, Sweta; Sharma, Vishnu; Yesudas, Rincy; Rajput, Ritu Singh (Journal of Biomedical and Pharmaceutical Research, 2019)
The medicinal plants have been used for years in daily life to treat infections all over the world. Azadirachta indica is a very valuable traditional therapeutic plant in the sub-continent regions. Each part of the tree has remarkable medicinal properties. In the present study, Phytochemical study yielded positive results for tannins, cardiac glycosides, anthraquinones, and saponins. The terpenoids was found to be missing. In antimicrobial studies, the organic and aqueous Leaf extract of Azadirachta indica found to show inhibitory action against the growth of Staphylococcus aureus and Escherichia coli that reveal the presence of pharmacologically bioactive constituents in Azadirachta indica. Key words: Nature; Azadirachta indica; Ayurveda; antimicrobial activity